2023
DOI: 10.3390/economies11100252
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness and Unemployment in Selected Southern African Development Community (SADC) Countries

Dorcas Gonese,
Kin Sibanda,
Phillip Ngonisa

Abstract: The relationship between trade openness and unemployment in Southern African Development Community (SADC) countries remains an area of significant interest and concern. While trade openness is often advocated for fostering economic growth and development, its potential effects on employment outcomes are complex and multifaceted. Understanding the nature and nuances of this relationship within the SADC region is crucial for policymakers and stakeholders seeking to design effective strategies that balance the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In that case, these two groups are the ones that suffer, since there is a probability that those low-level jobs that young or uneducated people are targeting would no longer exist with such a level of import. The results are in line with Mohler et al (2018), who found that import has a significant effect on the probability of becoming unemployed in the case of low-skilled workers, as well as the results of Gonese et al (2023), who proved the existence of a positive effect of import on unemployment. It should be noted, however, that these studies did not distinguish unemployment according to specific categories.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In that case, these two groups are the ones that suffer, since there is a probability that those low-level jobs that young or uneducated people are targeting would no longer exist with such a level of import. The results are in line with Mohler et al (2018), who found that import has a significant effect on the probability of becoming unemployed in the case of low-skilled workers, as well as the results of Gonese et al (2023), who proved the existence of a positive effect of import on unemployment. It should be noted, however, that these studies did not distinguish unemployment according to specific categories.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of import, Mohler et al (2018) found that import significantly affects the probability of becoming unemployed in the case of the lowskilled labor force. Gonese et al (2023) also found that import positively affects unemployment, but only in the long run. An opposite effect was detected by Jin et al (2019).…”
Section: Literature Reviewmentioning
confidence: 90%
See 2 more Smart Citations